Memahami Eksistensi dan Adaptasi Masyarakat Bersuku Batak di Kota Semarang - Anggraini, Anggi (Jurnal The Messenger, 2014)
This research intended to discover adaptation process and the existence of Batak tribe in Semarang as minority. Furthermore, this research could be used to break the ice of tension between Batak tribe and Java tribe, if there was any barrier before.  The method is qualitative descriptive,   in collecting data the researcher used observation and indepth interviews. Batak in Semarang is minority, but it   doesn t mean omitting its indigenous culture because of their settlement in new place, which is in Semarang. The existence of Batak culture is still going strong and supporting to adapt well. All of that is solely to receive positive recognition from the Java tribe, and demonstrate its strong sense of brotherhood.